Isolation and characterization of a Raf gene from Chinese shrimp Fenneropenaeus chinensis in response to white spot syndrome virus infection. Issue 83 (December 2018) - Li, Xupeng; Meng, Xianhong; Luan, Sheng; Luo, Kun; Cao, Baoxiang; Chen, Baolong; Kong, Jie
Abstract: Raf is a member in the Ras/Raf/MAPKK/MAPK signaling transduction pathway. To obtain a better understanding of Raf in the interaction between the Chinese shrimp Fenneropenaeus chinensis and white spot syndrome virus (WSSV), the sequence of cDNA of Raf from F . chinensis ( FcRaf ) was obtained. The FcRaf gene contained a 2421 bp open reading frame (ORF). The FcRaf shared most characteristic of Raf protein, such as the Raf-like Ras-binding domain (RBD), phorbol esters/diacylglycerol binding domain (C1 domain), and catalytic domain of the serine/threonine kinases, Raf (STKc_Raf). The sequence of functional domains of Raf protein was relatively conserved. The FcRaf mRNA was detected in the tissues of gill, muscle, and hepatopancreas from normal F . chinensis . The mRNA abundance level of FcRaf in the gill was the highest, which was 2.7-fold the level in the hepatopancreas. The expression level of FcRaf was significantly ( P  < 0.05) up-regulated in the tissues of gill, muscle, and hepatopancreas post WSSV-infection, which suggested that FcRaf might be involved in the interaction between F . chinensis and WSSV. Two SNP loci were identified in the ORF, one of which was a C-T mis-sense mutation, where an Ala was replaced by a Val, and induced the predicted protein secondary structure change. Considering the relatively low MAF (0.07), whether this mis-sense mutation was a detrimental mutation needs further investigation. Highlights: A cDNA encoding Raf from Fenneropenaeus chinensis ( FcRaf ) was cloned and sequenced for the first time. The sequence of functional domains of FcRaf protein was relatively conserved. The FcRaf mRNA abundance level in tissues fluctuated post WSSV challenge. Two SNPs were identified in the FcRaf ORF and one of which was a mis-sense mutation.